2018
DOI: 10.3390/v10070340
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Flaviviruses and the Type I Interferon Response

Abstract: Flaviviruses are globally distributed pathogens causing millions of human infections every year. Flaviviruses are arthropod-borne viruses and are mainly transmitted by either ticks or mosquitoes. Mosquito-borne flaviviruses and their interactions with the innate immune response have been well-studied and reviewed extensively, thus this review will discuss tick-borne flaviviruses and their interactions with the host innate immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 185 publications
(267 reference statements)
0
29
0
Order By: Relevance
“…Two studies have reported a recombination event between LIV and TBEV-Eu [ 20 , 24 ]; however, subsequent work has raised doubts about these findings [ 25 ]. Although the geographic ranges of the two viruses are largely distinct [ 26 ], creating limited opportunities for interaction, recent detection of TBEV in Britain [ 27 29 ], where LIV is endemic, has added new urgency to investigate the possibility of recombination between the two viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have reported a recombination event between LIV and TBEV-Eu [ 20 , 24 ]; however, subsequent work has raised doubts about these findings [ 25 ]. Although the geographic ranges of the two viruses are largely distinct [ 26 ], creating limited opportunities for interaction, recent detection of TBEV in Britain [ 27 29 ], where LIV is endemic, has added new urgency to investigate the possibility of recombination between the two viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Some important PRRs during infection of RNA viruses are Toll-like receptors (TLRs) 3, 7, 8 and 9 or retinoic-acid-inducible gene I (RIG-I)-like receptors. Their activation leads to the production of type I interferon (IFN) (reviewed in [ 68 ]), which was shown to have a protective role in TBEV infection (reviewed in [ 69 ]). Besides the crucial role of innate immune cells to combat TBEV, there is evidence that some of these cells are infected by TBEV, favor viral spread or contribute to pathogenesis in TBEV infection.…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 99%
“…Besides the crucial role of innate immune cells to combat TBEV, there is evidence that some of these cells are infected by TBEV, favor viral spread or contribute to pathogenesis in TBEV infection. Some non-structural proteins of TBEV, such as NS1, NS2A, NS4A, NS4B or NS5, display antagonistic functions, thus, interfering with components of the innate immune response (reviewed in [ 3 , 69 , 70 , 71 , 72 ]; [ 73 ]). In addition, TBEV infection modulates expression patterns of many antiviral genes which are involved in the innate immune response such as genes for PRRs, cytokines or chemokines [ 74 ].…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 99%
“…Two studies have reported a recombination event between LIV and TBEV-Eu (19, 23); however, subsequent work has raised doubts about these findings (24). Although the geographic ranges of the two viruses are largely distinct (25), creating limited opportunities for interaction, recent detection of TBEV in Britain (2628), where LIV is endemic, has added new urgency to investigate the possibility of recombination between the two viruses.…”
Section: Introductionmentioning
confidence: 99%